AN EVALUATION STUDY OF BILINGUAL PROGRAM IN SMA NEGERI 1 DENPASAR - Ni Putu, Astiti Pratiwi; Putu, Kerti Nitiasih (Jurnal Pendidikan Bahasa Inggris, 2013)
This study aimed at describing and explaining the implementation of Bilingual Program in SMA Negeri 1 Denpasar. It was an evaluation study which used CIPP model of evaluation. Being a qualitative study, it focused on describing and explaining the implementation of bilingual education in SMA Negeri 1 Denpasar in terms of context, input, process and product components. The subjects of this study were the English teachers , headmaster and the students of SMA Negeri 1 Denpasar in academic year 2012/2013. The data were in the form of : 1) researcherâs notes of the teaching and learning observation, 2) transcript of interview with the headmaster, English teachers, and the students, 3) teachersâ academic document, and 4) schoolâs documents. The main instrument was the researcher herself. The data were analyzed using Interactive Model of Miles and Hubermanâs (1994). The findings of the study were divided into 4 sections, which were concerned with context, input, process and product respectively. The context components examined in this study include the reason why SMA Negeri 1 Denpasa becomes RSBI. The input components are the curriculum, studentsâ entry selection, educator and educational staff, and infrastructure. The process component is the teaching and learning process of bilingual program in the English class. The product is the studentsâ score on the English competency. In terms of context, this school becomes RSBI because it can fulfil the requirements from the government, and also made proposal for being so. Â For the input, the school already follows the regulation of R-SMABI about the SNP+X. The school uses a curriculum called adaptive curriculum, which is a result of adaptation from 3 curricula, namely KTSP SMA N 1 Denpasar, Cambridge curriculum, and General certificate of Singapore Education. In terms of Educator and educational staff, 18.84 % of the teachers have post graduate qualification. The school employs the entrance system using TPA and psycho test. In the process, the teaching and learning process already implement bilingual education, but still have lots of weaknesses. In terms of product, all of the students in SMA Negeri 1 Denpasar are able to pass the KKM. Keywords: evaluation study, CIPP, bilingual program.